Research and educational system of Islamic world in the globalisation era / Hasan Noorbakhsh - Noorbakhsh, Hasan (2010)
The object of this article is the analysis to the question that how can research and educational systems of the Islamic world in the globalization era answer to the challenges and thinking problems facing its present era? In other words, with what strategy and function can the research and educational systems of the Islamic world play an active role in the contemplative realm of this globalisation era? In order to answer these questions we have briefly analysed the effects of globalisation on culture, thinking and education and then we have looked at the role and function of the education and research system of the Islamic world in the globalisation era.